Marine Important Bird and Biodiversity Areas in the Chagos Archipelago. (26th August 2023) - Carr, Peter; Trevail, Alice M.; Koldewey, Heather J.; Sherley, Richard B.; Wilkinson, Tim; Wood, Hannah; Votier, Stephen C.
Summary: Seabirds are declining globally and are one of the most threatened groups of birds. To halt or reverse this decline they need protection both on land and at sea, requiring site-based conservation initiatives based on seabird abundance and diversity. The Important Bird and Biodiversity Area (IBA) programme is a method of identifying the most important places for birds based on globally agreed standardised criteria and thresholds. However, while great strides have been made identifying terrestrial sites, at-sea identification is lacking. The Chagos Archipelago, central Indian Ocean, supports four terrestrial IBAs (tIBAs) and two proposed marine IBAs (mIBAs). The mIBAs are seaward extensions to breeding colonies based on outdated information and, other types of mIBA have not been explored. Here, we review the proposed seaward extension mIBAs using up-to-date seabird status and distribution information and, use global positioning system (GPS) tracking from Red-footed Booby Sula sula – one of the most widely distributed breeding seabirds on the archipelago – to identify any pelagic mIBAs. We demonstrate that due to overlapping boundaries of seaward extension to breeding colony and pelagic areas of importance there is a single mIBA in the central Indian Ocean that lays entirely within the Chagos Archipelago Marine Protected Area (MPA). Covering 62, 379 km 2 it constitutes 10% of the MPA and if designated, would become the 11 th largest mIBA in the world and 4 th largest in the Indian Ocean. Our research strengthens the evidence of the benefits of large-scale MPAs for the protection of marine predators and provides a scientific foundation stone for marine biodiversity hotspot research in the central Indian Ocean.